Instructional Methodological Class. An Experience In The Physiological Sciences Of Guantánamo. Cuba - Betancourt Pulsan, Anselma; Terrado Quevedo, Sara Terrado Quevedo; Romero Barrientos, Caridad Romero Barrientos; Perez Villalón, Elbis Perez Villalón (Revista Cubana de Investigaciones Biomédicas, 2019)
<!--[if gte mso 9]> <![endif]--> The methodological class is the type of teaching-methodological work that, through demonstration, argumentation and analysis, guides teachers on some aspects of a methodological nature that contribute to their preparation for the implementation of the educational process. The class can be of a demonstrative or instructive nature, and will respond to the methodological objectives formulated. The importance of the methodological teaching class for young teachers of the Basic Sciences in particular and from the assumption that the classes are classified on the basis of the objectives to be achieved and their main types are: the lecture, the practical class, the seminar, the meeting class, the laboratory practice and the workshop. The methodological conceptual problem was taken into account: Insufficiencies that are manifested in the young faculty of the faculty in the methodological structuring that requires the delivery of a laboratory practice. General Methodological Objective: To instruct young faculty members in the methodological structure that requires the delivery of a laboratory practice. When considering the relevance of the instructional methodological class it is praiseworthy to share the experience of an instructional methodological class from a laboratory practice, specifically related to the subject: Blood and Immune System. <!--[if gte mso 9]> Normal 0 21 false false false ES-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->